2020
DOI: 10.3390/molecules25215143
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Biogenic Amines Producers in the Wastewater of the Dairy Industry

Abstract: Out of six samples of wastewater produced in the dairy industry, taken in 2017 at various places of dairy operations, 86 bacterial strains showing decarboxylase activity were isolated. From the wastewater samples, the species of genera Staphylococcus, Lactococcus, Enterococcus, Microbacterium, Kocuria, Acinetobacter, Pseudomonas, Aeromonas, Klebsiella and Enterobacter were identified by the MALDI-TOF MS and biochemical methods. The in vitro produced quantity of eight biogenic amines (BAs) was detected by the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…The concentration of precursor amino acid used in this earlier study was 1,000-fold lower than that used here, and it was thus unlikely that our method failed to detect biogenic amine production by the K. rhizophila isolates. Jančová et al (2020) analyzed the ability of two K. rhizophila and one K. varians isolates from dairy wastewater to produce eight biogenic amines. Except for spermidine, the production of other biogenic amines was detected, with that of putrescine, cadaverine and tyramine being the most significant ( Jančová et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The concentration of precursor amino acid used in this earlier study was 1,000-fold lower than that used here, and it was thus unlikely that our method failed to detect biogenic amine production by the K. rhizophila isolates. Jančová et al (2020) analyzed the ability of two K. rhizophila and one K. varians isolates from dairy wastewater to produce eight biogenic amines. Except for spermidine, the production of other biogenic amines was detected, with that of putrescine, cadaverine and tyramine being the most significant ( Jančová et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“… Jančová et al (2020) analyzed the ability of two K. rhizophila and one K. varians isolates from dairy wastewater to produce eight biogenic amines. Except for spermidine, the production of other biogenic amines was detected, with that of putrescine, cadaverine and tyramine being the most significant ( Jančová et al, 2020 ). It should be noted that only the production of the biogenic amines of most concern was examined in the present study.…”
Section: Resultsmentioning
confidence: 99%
“…In an experiment done in 2017 by Jančová et al (2020), in two seasons (summer and autumn), wastewater samples were obtained from six offtake points that are linked to the processing of various dairy products and are crucial for the drainage of wastewater, as it is known, milk and dairy products represent a suitable environment for the growth of microorganisms, that may influence, through their metabolic activity (positively or negatively), the product quality. by Using the MALDI-TOF MS and biochemical methods, identified 77 bacterial strains belonging to 19 bacterial genera out of 89 isolated colonies, plus three fungi -Candida parapsilosis Metschnikowia pulcherrima, and Rhodotorula mucilaginosa were successfully identified.…”
Section: Application Of Maldi-tof Ms In the Identification Of Bacteri...mentioning
confidence: 99%
“…There are other studies conducted on MALDI-TOF MS in which high rates of bacteria are identified from different sources (wastewater, rural areas, etc.) [18][19][20]. It is increasingly preferred for the identification of Gram (-) bacteria of fecal origin from food and farm animals [21,22].…”
Section: Introductionmentioning
confidence: 99%